2020
DOI: 10.1007/s11356-019-06767-7
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic musk fragrances (PMFs) in wastewater and activated sludge: analytical protocol and application to a real case study

Abstract: Two different analytical methods for the determination of polycyclic musk fragrances (PMFs) in wastewater and in activated sludge were developed. PMFs in filtered water samples were determined by gas chromatography coupled with a triplequadrupole mass spectrometer in selected reaction monitoring (SRM) mode. Activated sludge samples were extracted using an ultrasonic bath and analysed using a GC-Ion trap. The developed methods respected a linear model (R 2 > 0.995). Detection limits of selected compounds (Celes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
2
4
2
Order By: Relevance
“…The HHCB concentration in the STP influents in this study was higher than that previously reported in Italy [34], Spain [35,36], France [22], and other studies in Korea [25] (Table S4). This might be due to the characteristics of the STPs, which were located in the densely populated city of Seoul, and most of the STP influents were therefore composed of domestic sewage.…”
Section: Synthetic Musk Fragrances In Stp Influentscontrasting
confidence: 79%
See 1 more Smart Citation
“…The HHCB concentration in the STP influents in this study was higher than that previously reported in Italy [34], Spain [35,36], France [22], and other studies in Korea [25] (Table S4). This might be due to the characteristics of the STPs, which were located in the densely populated city of Seoul, and most of the STP influents were therefore composed of domestic sewage.…”
Section: Synthetic Musk Fragrances In Stp Influentscontrasting
confidence: 79%
“…The HHCB/AHTN concentration ratio in the sewage influents was 16.4, which was higher than the previously reported values of 4.5 [25], 1.2 [28], and 3.2 [26], and similar to the value obtained by Tasselli and Guzzella [34]. This result implies that significantly higher amounts of HHCB than AHTN are used in PCPs in Korea.…”
Section: Synthetic Musk Fragrances In Stp Influentssupporting
confidence: 62%
“…The HHCB concentration in the STP influent in this study was higher than that previously reported in Italy [32], Spain [33,34], and France [19], and other studies in Korea [22] (Table S4). This might be due to the characteristics of the STPs, which were located in the densely populated city of Seoul, and most of the STP influents were therefore composed of domestic sewage.…”
Section: Synthetic Musk Fragrances In Stp Influentcontrasting
confidence: 78%
“…The detailed studies showed that it is liable to aerobic and anaerobic biotransformation [15] as well as to physical processes such as sorption onto active sludge [16]. Its removal efficiency is in the range of 30-99.7% and depends on the applied technology, the construction of the reactors and their numbers as well as the additional advanced oxidation modules used [15][16][17][18]. However, due to its widespread use and continuous supply to the treatment plants, it is perceived as a persistent pollutant [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its widespread use and continuous supply to the treatment plants, it is perceived as a persistent pollutant [1]. Its concentration in the WWTP influent ranges from 1.9 to 16 µg L −1 [15][16][17][18] and in the effluent from 0.2 to 7.0 µg L −1 [12,15,16,18]. It is found in surface waters at the relatively low level below 100 ng L −1 [5,12] while in drinking water detected at the trace level below 30 ng L −1 or below LOD of the applied analytical procedure [12].…”
Section: Introductionmentioning
confidence: 99%